2019
DOI: 10.1016/j.yjmcc.2019.03.024
|View full text |Cite
|
Sign up to set email alerts
|

C53: A novel particulate guanylyl cyclase B receptor activator that has sustained activity in vivo with anti-fibrotic actions in human cardiac and renal fibroblasts

Abstract: The native particulate guanylyl cyclase B receptor (pGC-B) activator, C-type natriuretic peptide (CNP), induces anti-remodeling actions in the heart and kidney through the generation of the second messenger 3',5' cyclic guanosine monophosphate (cGMP). Indeed fibrotic remodeling, particularly in cardiorenal disease states, contributes to disease progression and thus, has been a key target for drug discovery and development. Although the pGC-B/cGMP system has been perceived as a promising anti-fibrotic pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
0
30
0
1
Order By: Relevance
“…However, NPR-B heterozygote mice are susceptible to aortic stenosis [148], suggesting that the importance of this NPR subtype might sit outside the cardiomyocyte. This does not mean that NPR-B cannot be targeted pharmacologically, as recent studies suggest that novel designer peptides that bind to NPR-B can reduce fibroblast proliferation and collagen secretion in vitro and in vivo [128,149,150]. This role of endogenous NPR-C signalling in regulating fibrosis is supported by other studies that have observed greater cardiac dysfunction, atrial collagen deposition, and higher levels of TGFβ and TIMP1 in NPR-C KO mice subjected to angiotensin II-induced pressure overload [151,152].…”
Section: Endogenous Cnp Is Cardioprotective In Animal Models Of Hementioning
confidence: 99%
“…However, NPR-B heterozygote mice are susceptible to aortic stenosis [148], suggesting that the importance of this NPR subtype might sit outside the cardiomyocyte. This does not mean that NPR-B cannot be targeted pharmacologically, as recent studies suggest that novel designer peptides that bind to NPR-B can reduce fibroblast proliferation and collagen secretion in vitro and in vivo [128,149,150]. This role of endogenous NPR-C signalling in regulating fibrosis is supported by other studies that have observed greater cardiac dysfunction, atrial collagen deposition, and higher levels of TGFβ and TIMP1 in NPR-C KO mice subjected to angiotensin II-induced pressure overload [151,152].…”
Section: Endogenous Cnp Is Cardioprotective In Animal Models Of Hementioning
confidence: 99%
“…2A). We further treated a pool of plasma samples with neuraminidase to remove only terminal sialic acid residues, followed by immunoprecipitation and detection using pAb proANP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , and this resulted in a mobility shift of the slower migrating 14 kDa band by ϳ1-2 kDa (Fig. 2B).…”
Section: Identification Of Partially O-glycosylated Proanp 1-98 In Humentioning
confidence: 99%
“…Anesthesia in rats was induced with 133 mg/kg intraperitoneal inactin (Sigma), and rats were maintained on a heating pad for 1 h until complete anesthesia was achieved. With oxygen flow, the rats were then subjected to catherizations and blood and urine collections (2). A polyethylene (PE)-50 tube catheter was placed into the jugular vein for intravenous (i.v.)…”
Section: In Vivo Evaluation Of Glycosylated Anpmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of neprilysin inhibition provides modulatory effect on endogenous vasoactive peptides such as natriuretic peptides and bradykinin, resulting in beneficial remodelling and vasodilation (D'Elia et al, 2017). Given the therapeutic success of sacubitril–valsartan via natriuretic peptide augmentation, designer natriuretic peptide analogues such as MANP (also known as ZD100) (McKie et al, 2014), CRRL‐269 (Chen, Harty, et al, 2019), NPA7 (Meems et al, 2019), C53 (Chen et al, 2019) or cenderitide (also known as CD‐NP) (Kawakami et al, 2018) may offer an alternative, yet complementary, therapeutic strategy for cardiorenal syndrome and are currently under advanced preclinical and clinical development. Empagliflozin and canagliflozin, sodium‐glucose cotransporter 2 (SGLT2) inhibitors, demonstrated beneficial cardiovascular and all‐cause mortality and hospitalization in diabetic patients with high cardiovascular risk (Zinman et al, 2015).…”
Section: Diagnosis Prognosis and Treatment Of Cardiorenal Syndromementioning
confidence: 99%